Visions of America in American postmodern poetry: The Case of Allen Ginsberg’s Howl - BESSERIANI, Hamza; SADAOUI, Med El-khames (جامعة الوادي - University of Eloued, 2023)
الملخص: تعتبر فترة ما بعد الحداثة من أشهر الفترات الذي مرت على تاريخ الادب الامريكي والتي ظهرت بعد الحرب العالمية الثانية. تناقش هذه الدراسة أشهر اعمال الشاعر ألن غينسبرغ والمسماة "عواء". تهدف هذه المذكرة لإظهار تميز أسلوب ومحتوى غينسبرغ مقارنة بأقرانه من الشعراء ولمعرفة كيف قام بكتابة شعره بخصائص جديدة لإيصال رؤيته حول الظروف السائدة في فترته. لقد قمنا بهذه الدراسة لإظهار القيمة الفنية لهذا الشعر واهميته وليس فقط كنقد لمجتمعه وكذلك لإعطاء فهم معمق له. قمنا بتحليل هذا الشعر باستعمال منهج جوفري ليتش وميك شورت وصادفنا الكثير من السمات الاسلوبية مثل السمات المعجمية، الجناس، الحقل المعجمي، السمات النحوية والخطية. بالإضافة الى ذلك راجعنا العديد من الكتب والمقالات التي ناقشت وحللت هذا الشعر لجمع اهم المعلومات حول غينسبرغ وعمله. من اهم نتائج هذه الدراسة هي معرفة مختلف نظرات غينسبرغ لأمريكا ومنها الراس مالية، الجنسية، المعاناة، الحياة المدنية، الثقافة المضادة، القمع، النزعة المادية والاستهلاكية، الفقر والامراض العقلية. واخيرا، الشعر الامريكي في فترة ما بعد الحداثة اعطى دفعة قوية في الادب وخاصة القصيدة "عواء" التي خلفت تأثيرا عميقا في الادب والمجتمع الأمريكي American postmodern poetry is one of the well-known areas in American literary history. It appeared after the World War II. This study discussed the famous work of Ginsberg which is Howl. It aims to investigate the uniqueness of Ginsberg's thoughts as compared to other American poets and to know how he constructed his poem with new features at that time to convey his vision about America. We carried out this study to demonstrate that this poem is a piece of art with artistic value and significance, and not just a social critique, and to provide a deeper understanding of the poem. By using Geoffrey Leech and Mick short’s literary stylistic approach, we analyzed the poem and we found different stylistic features such as lexical deviation, anaphora, lexical cohesion, phonological deviation and graphological deviation. Also, we reviewed several literary books and articles that discussed and analyzed the poem in order to gather the information about Ginsberg and his work. The main results of this study are knowing the different visions of Ginsberg toward America such as capitalism, sexuality, suffering, urban life, counterculture, repression, materialism and consumerism, poverty and mental illness. In the conclusion, American postmodern poetry gave breakthrough in the literature and especially Howl that had significant impact on literature and the American society because of Ginsberg’s visions of America in the poem.
Master’s Degree in Literature and Civilization
Keywords: عواء، رؤى، شعر، السمات الاسلوبية، ألن غينسبرغ، أمريكا; Allen Ginsberg, America, Howl, Poetry, stylistics, Visions.